ROLE OF THE ENDOTHELIAL SYSTEM IN THE DEVELOPMENT OF HYPERTENSION IN PREGNANT WOMEN - Djamilova H. A. (Modern American Journals, 2025)
In recent years, the role of the vascular endothelium in the pathogenesis of the development of critical conditions, including the development of gestational complications, has received increasing attention. This review presents current literature data on the role of endothelial dysfunction in the development of hypertensive conditions during pregnancy.
Keywords: Pregnancy, hypertension, preeclampsia.